Concomitant off-pump coronary artery bypass grafting and total thyroidectomy for a large retrosternal goitre: a case report and review of the literature - Lampridis, Savvas; Lau, Man Chi; Mhandu, Peter; Parissis, Haralabos (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
A 76-year-old male presented with angina and a large retrosternal goitre causing marked dyspnoea. Coronary angiography revealed triple vessel disease and moderately impaired left ventricular function. CT imaging demonstrated a substantial multinodular goitre extending into the posterior mediastinum to the level of the carina, with associated compression of the trachea and oesophagus. Preoperative thyroid function tests showed euthyroid state. The patient subsequently underwent off-pump coronary artery bypass grafting (OPCABG) ×2 with concomitant total thyroidectomy. A thyroid mass of dimensions 19 cm × 16 cm × 5.5 cm and weight 439 g was confirmed to be a multinodular goitre. Postoperative complications included bilateral recurrent laryngeal nerve damage, hypocalcaemia and ventilator-associated pneumonia. The patient was discharged 36 days postoperatively and remained asymptomatic at 1 year follow up. This case provides further evidence that concomitant OPCABG and thyroidectomy for the treatment of large retrosternal goitre can be safely and effectively performed, provided that perioperative levels of thyroid hormones are maintained at euthyroid or hypothyroid levels.